Sosialisasi Pemberdayaan Remaja Perempuan dalam Menyikapi Tantangan Hak dan Privasi Digital di Era AI dan Media Sosial : Studi Kasus di SMA Negeri Wangon - Apitta Rahmawati; Yuris Tri Naili; Marlia Hafny Afrilies (Nusantara Mengabdi Kepada Negeri, 2025)
The advancement of artificial intelligence (AI) technology and social media has significantly influenced the dynamics of societal life, including women. Social media offers a space for the empowerment of women, but at the same time, it also presents various risks such as privacy violations, digital violence, and misuse of personal data. This community service activity aims to strengthen digital literacy among women, particularly in raising awareness of digital risks, protecting digital rights, and promoting safe and responsible social media use. The implementation methods of the activities include outreach in the form of workshops, discussion forums, and case simulations. The results of the activities indicate that there has been an increase in participants' knowledge about privacy in the digital world, forms of gender-based violence in the online realm, and strategies for preventing digital risks. This program is expected to serve as a model for empowering women through the enhancement of digital literacy in responding to the challenges of an increasingly digitalized era.